Determination of the LC50 and evaluation of the genotoxic activity of arsenic on nucleated erythrocytes from the peripheral blood of zebrafish (Danio rerio, Hamilton, 1822) - Scotto, Carlos (2023)
The importance of the zebrafish (Danio rerio, Hamilton, 1822) as an animal model to understand how various biological processes occur due to genotoxicity is well known. In the present investigation, the LC50 (median lethal concentration) was obtained in zebrafish for arsenic (As), which was 0.3 mg. L-1. Peripheral blood was then used to visualize genotoxic damage caused by As in nucleated erythrocytes using the comet assay. All types of comets were found according to the As concentration, type 0 (without damage) in the control and in the rest from LC50 all types of comets were present, type 3 and 4 (severe and serious damage) being more abundant. Concentrations 1/10, 1/5 and 1/2 of the LC50 showed comet types 1 and 2 more frequently, demonstrating the high sensitivity of the comet assay and the great versatility as an animal model of the zebrafish.